2020
DOI: 10.1002/hep.30912
|View full text |Cite
|
Sign up to set email alerts
|

Sox9 Is a Modifier of the Liver Disease Severity in a Mouse Model of Alagille Syndrome

Abstract: Background and Aims Alagille syndrome (ALGS) is a multisystem developmental disorder characterized by bile duct (BD) paucity, caused primarily by haploinsufficiency of the Notch ligand jagged1. The course of the liver disease is highly variable in ALGS. However, the genetic basis for ALGS phenotypic variability is unknown. Previous studies have reported decreased expression of the transcription factor SOX9 (sex determining region Y‐box 9) in late embryonic and neonatal livers of Jag1‐deficient mice. Here, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 50 publications
5
39
0
Order By: Relevance
“…Furthermore, removing both copies of Sox9 in Jag1 +/– livers further worsened the phenotypes and resulted in ~50% lethality by P25 [39]. In agreement with studies on other models of Notch deficiency in the liver [15,35,42], the Jag1 +/– biliary defects showed significant improvement by age [39]. Again, simultaneous loss of one copy of Sox9 prevented this improvement in Jag1 +/– mice.…”
Section: The Role Of Notch Signaling and Its Modifiers In The Pathsupporting
confidence: 63%
See 3 more Smart Citations
“…Furthermore, removing both copies of Sox9 in Jag1 +/– livers further worsened the phenotypes and resulted in ~50% lethality by P25 [39]. In agreement with studies on other models of Notch deficiency in the liver [15,35,42], the Jag1 +/– biliary defects showed significant improvement by age [39]. Again, simultaneous loss of one copy of Sox9 prevented this improvement in Jag1 +/– mice.…”
Section: The Role Of Notch Signaling and Its Modifiers In The Pathsupporting
confidence: 63%
“…As mentioned before, in a Notch-sufficient condition, loss of both copies of Sox9 results in a mild delay in biliary development that recovers by 5 weeks of age [27]. However, we found that conditional loss of one copy of Sox9 by using the Albumin-Cre transgene in the context of Jag1 heterozygosity worsens the Jag1 +/– biliary phenotypes, as assessed by liver histology, serum chemistry and 3D visualization of the biliary tree [39]. Furthermore, removing both copies of Sox9 in Jag1 +/– livers further worsened the phenotypes and resulted in ~50% lethality by P25 [39].…”
Section: The Role Of Notch Signaling and Its Modifiers In The Pathmentioning
confidence: 56%
See 2 more Smart Citations
“…There are a number of mouse models for ALGS [15][16][17] , which recapitulate important aspects of ALGS (reviewed in 18 ). We recently developed a model for ALGS, in a mixed C3H/C57bl6 genetic background, harboring a single nucleotide substitution resulting in a H268Q amino acid change in EGF-like repeat 2 of Jagged1 19 .…”
Section: Introductionmentioning
confidence: 99%